Public spending at the district level in Ghana - Osei-Akoto, Isaac; Osei, Robert Darko; Quarmine, William; Adiah, George Adayi-Nwoza (International Food Policy Research Institute, 2007)
Public spending may influence poverty alleviation objectives at several levels including overall spending plans of government (aggregate fiscal policy), policy decisions funded in the budget and the flow of budgeted resources to Ministries, Department and Agencies (MDAs); frontline service delivery institutions whose activities directly impact the development outcomes. As a starting point for analysis of the returns of public spending at the district level, this short report attempts to review the trends in financial inflows and outlays from District Assemblies (DAs) and link them to key development outcomes over the period spanning 1994 to 2004... It is important to note that this report is mainly descriptive and intended to provide preliminary explanation of the relationship between public expenditures and district level development outcomes.